The Potential Use of Pharmacological Agents to Modulate Orthodontic Tooth Movement (OTM) - Kouskoura, Thaleia; Katsaros, Christos; von Gunten, Stephan (Frontiers in Physiology, 2017)
The biological processes that come into play during orthodontic tooth movement (OTM) have been shown to be influenced by a variety of pharmacological agents. The effects of such agents are of particular relevance to the clinician as the rate of tooth movement can be accelerated or reduced as a result. This review aims to provide an overview on recent insights on drug-mediated effects and the potential use of drugs to influence the rate of tooth movement during orthodontic treatment. Limitations of current experimental models and the need for well-designed clinical and pre-clinical studies are also discussed.